Self Defense is Killing Us - Hollas, Deanna (2022)
Much of the gun violence prevention debate has been around gun control and personal responsibility when the focus should be on the hidden power and influence of the gun industry that has shaped the narrative in order to maximize profit and stay in business. This article unmasks the gun industry’s marketing strategy so that we can begin to have a different conversation around what actually makes us safe and take action to end gun violence.
Keywords: White Supremacy; Trauma; Disarm; Suicide; School Shooting; Gun Industry; Gun Manufacturing; Guns